Development and Validation of Competitive ELISA for Detection of H5 Hemagglutinin Antibodies - Orie Hochman; Wanhong Xu; Ming Yang; Chengbo Yang; Aruna Ambagala; Anna Rogiewicz; Joseph J. Wang; Yohannes Berhane (Poultry, 2023)
Influenza A viruses (IAVs) belonging to the goose/Guangdong (Gs/GD)-lineage H5Nx remain a major concern for the global poultry industry, wildlife, and humans. The hemagglutinin (HA) protein is the dominant antigenic epitope carrier within IAV, which in turn triggers substantial immunogenic responses in the infected host. The current study describes the development and validation of a highly sensitive competitive H5 ELISA (cELISA) based on a novel monoclonal antibody developed in mice immunized with inactivated virus H5N1 (A/Turkey/ON/6213/1966). The cELISA is capable of detecting the H5 antibody response to a wider range of H5-subtype viruses belonging to both North American and Eurasia lineages, including the Gs/GD H5Nx from clade 2.3.4.4b that is currently causing the highly pathogenic avian influenza outbreaks in Eurasia, Africa, and Latin and North America. The developed H5 cELISA provides a specific, sensitive, and species-independent serological assay for the rapid detection of H5 antibodies. The assay is more robust and more sensitive than the hemagglutination inhibition assay, which is the “Gold standard”. The assay can be used in serological diagnosis, serosurveillance, and vaccine monitoring of serum samples collected from different species of animals.